A SARS‐CoV‐2 Neutralization Assay Using Single Molecule Arrays. Issue 49 (5th November 2021) - Gilboa, Tal; Cohen, Limor; Cheng, Chi‐An; Lazarovits, Roey; Uwamanzu‐Nna, Augusta; Han, Isaac; Griswold, Kettner; Barry, Nick; Thompson, David B.; Kohman, Richie E.; Woolley, Ann E.; Karlson, Elizabeth W.; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) manifests with high clinical variability and warrants sensitive and specific assays to analyze immune responses in infected and vaccinated individuals. Using Single Molecule Arrays (Simoa), we developed an assay to assess antibody neutralization with high sensitivity and multiplexing capabilities based on antibody‐mediated blockage of the ACE2‐spike interaction. The assay does not require live viruses or cells and can be performed in a biosafety level 2 laboratory within two hours. We used this assay to assess neutralization and antibody levels in patients who died of COVID‐19 and patients hospitalized for a short period of time and show that neutralization and antibody levels increase over time. We also adapted the assay for SARS‐CoV‐2 variants and measured neutralization capacity in pre‐pandemic healthy, COVID‐19 infected, and vaccinated individuals. This assay is highly adaptable for clinical applications, such as vaccine development and epidemiological studies. Abstract : Using Single Molecule Arrays (Simoa), we developed a simple neutralization assay based on antibody‐mediated blockage of the ACE2‐spike interaction. This assay can assess antibody neutralization with high sensitivity and multiplexing capabilities. We used this assay to profile neutralization capacity in patients infected with SARS‐CoV‐2 and vaccinated individuals and show that this assay is useful for various clinical applications.